Internationalisation in Higher Education: Post-Covid Trends of Students' Mobility (Case Study EUROMED Countries) - Nada Trunk Širca; Anica Novak Trunk; Touhami Abdouli; Anwar Kawtharani (International School for Social and Business Studies, 2024)
Purpose: This article examines trends in the internationalisation of higher education within the Euro-Mediterranean (EUROMED) region, with a particular focus on student mobility as a driving force for fostering academic collaboration across borders. Study design/methodology/approach: The research uses data from UNESCO to analyse student movement patterns in 23 Euro-Mediterranean countries. It considers key factors influencing these trends, including economic incentives, geopolitical stability, and cultural linkages. It also assesses the impact of the COVID-19 pandemic on international student mobility and the adaptation of physical, virtual, and blended mobility formats to new realities. Findings: The findings highlight that while physical mobility remains essential, the rise of virtual and blended mobility options post-pandemic has introduced more inclusive and accessible student pathways. This shift enhances the resilience and adaptability of internationalisation frameworks within the EUROMED region, enabling a more robust response to the fluctuating global conditions. Originality/value: This study provides a comprehensive look at the unique cultural, geopolitical, and educational context of the EUROMED region. It underscores the importance of innovative mobility models in creating a more inclusive internationalisation approach that can withstand external challenges, particularly in a post-pandemic landscape.